Uji Antioksidan Ekstrak Etanol 70%, N-Heksan, Etil Asetat Biji Alpukat (Persea Americana Mill) dengan Metode DPPH - Putri Wahyu Ningrum; Supriyanto; Estuningtyas Ayu Hapsari (Yayasan Citra Dharma Cindekia, 2024)
Avocado (Persea americana Mill) is a fruit that is popular with many people, because it contains various nutrients. However, the use of avocados is not accompanied by the use of the seeds. Avocado seeds are usually used as antioxidants. Antioxidants are substances that the body needs to neutralize free radicals and prevent damage caused by free radicals. The aim of this research was to determine the antioxidant activity of avocado seed extract (Persea americana Mill) using the DPPH method. Avocado seed extract was extracted by soxhletation with different solvents 70% ethanol, n-hexane, and ethyl acetate. The extract obtained was identified for chemical compound content. Test antioxidant activity using the DPPH method to determine a good IC50 value. Based on the research results, the antioxidant test with different solvents that obtained a good IC50 value was n-hexane solvent with an IC50 value of 2.14µg/ml. The conclusion of the research is that good antioxidant test results with n-hexane solvent obtained an IC50 value of 2.14µg/ml, the lower the IC50 value, the higher the antioxidant.